Estimation of genetic parameters and environmental effects on somatic cell count in Simmental and Holstein breeds - Zdenko Ivkić; Marija Špehar; Vesna Bulić; Pero Mijić; Ante Ivanković; Drago Solić (Mljekarstvo, 2012)
The objective of this study was to estimate genetic parameters and environmental effects on somatic cell count in Croatian dairy cows. Data consisted of 861,417 test-day records for Simmental and 656,272 for Holstein cows. For Simmental breed, number of animals in pedigree was 123,199, while pedigree file for Holstein breed included 94,294 animals. A single-trait repeatability fixed regression test-day model was used to estimate genetic parameters. Fixed effects in the model were parity and calving season. Days in milk was fitted using Ali-Schaeffer lactation curve nested within parity. Age at first calving was modelled as quadratic regression. Direct additive genetic effect, herd, herd-test-date, and permanent environmental effect of cow within parity were included in the model as random effects. Variance components were estimated using Residual Maximum Likelihood method as implemented in the VCE-6 program. Estimated heritabilities were 0.21 for Simmental and 0.15 for the Holstein breed. Permanent environmental effect explained 19 % of phenotypic variation in Simmental and 20 % in Holstein breed. Herd and herd-test-date accounted for another 9 % and 5 % of variability for Simmental breed. The effects of herd and herd-test-date explained 10 % and 5 % of phenotypic variance in Holstein breed.